Relationship between miR-21, TLR4 and ventricular remodeling and prognosis in elderly patients with acute coronary syndrome - Gu Peipei; Wang Haitao; Wei Xiaohui (Guoji laonian yixue zazhi)
[Objective] To investigate the relationship between miR-21, Toll-like receptor 4(TLR4) and ventricular remodeling and prognosis in elderly patients with acute coronary syndrome (ACS). [Methods] A total of 100 elderly patients with ACS who received treatment in the People’s Hospital of Xinjiang Uygur Autonomous Region from January 2020 to December 2022 were selected as the case group, and 100 healthy subjects in the same period were selected as the control group. Serum miR-21 and TLR4 expression and left ventricular remodeling parameters were measured and compared between the two groups, and Pearson correlation was used to analyze the correlation between miR-21 and TLR4 and ventricular remodeling parameters. After 1 year of follow-up, the patients were divided into good prognosis group (66 cases) and poor prognosis group (34 cases) according to whether major adverse cardiovascular events occurred. The serum miR-21 and TLR4 expression levels, ventricular remodeling indicators and related clinical data were compared between poor prognosis group and good prognosis group, and the relationship between miR-21, TLR4 and prognosis was analyzed. [Results] The levels of miR-21, TLR4, left ventricular mass index(LVMI), mean wall stress(MWS), and relative wall thickness(RWT) in the case group were higher than those in the control group (P<0.05); Pearson correlation analysis results showed that miR-21 and TLR4 were positively correlated with LVMI, MWS, and RWT (P<0.05). There were significant differences in age, diabetes, hypertension, and serum miR-21, TLR4, LVMI, MWS, and RWT levels between the good prognosis group and the poor prognosis group (P<0.05); logistic regression analysis showed that high miR-21 and TLR4 expression, LVMI, MWS, and RWT levels were independent risk factors for poor prognosis in elderly ACS patients (P < 0.05). The ROC curve results showed that the AUCs of miR-21 and TLR4 for predicting poor prognosis in elderly ACS patients were 0.878 and 0.778, respectively, both of which had good predictive efficacy (P<0.05). [Conclusion] The expression levels of miR-21 and TLR4 in serum of elderly patients with ACS were significantly increased, which were closely related to ventricular remodeling and prognosis, and had good predictive efficacy for prognosis.